Design and Build Learning Media to Read and Write Al-Qur'an Flash-Based - Tri Yusnanto; Khoirul Mustofa; Sugeng Wahyudiono; Uwe Barroso; Gergely Maja (Yayasan Adra Karima Hubbi, 2023)
The low motivation of students/santri in learning the Koran is still one of the causes of the low quality of education, especially in the ability to read the Koran. One of the efforts to increase the motivation of students/students in learning to read the Qur'an is by using the appropriate method. Along with the development of information technology, especially in the advancement of multimedia-based teaching media, the teaching of the Qur'an can use media more effectively. The design and development of this media uses a software development model with research stages including: data collection, analysis, design, implementation and report writing. The stages of data collection were carried out using the method of literature study and interviews, while in the analysis stage, the MDLC method was used. At the design stage a structured approach is used. Process design is carried out using flow chart tools. The results of the process design are used as a basis for developing user interface designs. The design of the resulting learning media was developed using Adobe Flash CS 4 and Adobe Flash CS 6 software. With this design, it is hoped that TPA Miftakhul Jannah Mosque can increase students' learning motivation in reading the Qur'an